Differentiating ASD from DLD in toddlers - Paul, Rhea; Chawarska, Katyrzyna; Volkmar, Fred R (Perspectives on Language Learning and Education, 2008)
Keywords: dept.cmd

Language outcomes of toddlers with autism spectrum disorders: A two year follow-up - Paul, Rhea; Chawarska, Katarzyna; Cicchetti, Domenic; Volkmar, Fred (Autism Research, 2008)
Thirty-seven children 15-25 months of age received clinical diagnoses of autism spectrum disorder (ASD) and were re-evaluated two years later. All subjects were judged to have retained a diagnosis of ASD at the follow-up evaluation. Communication scores for the group as a whole during the first visit were significantly lower than nonverbal IQ. However, by the second visit, verbal and nonverbal scores were no longer significantly different. The group was divided into two subgroups, based on expressive language (EL) outcome at the second visit. The two groups were similar in the second year of life in terms of expressive communication skills and autistic symptoms, except for a trend toward more stereotypic and repetitive behavior in the worse outcome group. By the second visit, however, the groups differed significantly on all standard measures of expression and reception, as well as on autistic symptomotology and nonverbal IQ. When assessed during their second year, children who ended up in the better outcome group showed higher average nonverbal cognitive level, receptive language (RL) scores, number of sounds and words produced, use of symbolic play schemes, and response to joint attention bids. Regression analysis revealed that the variables for which significant differences between the two outcome groups in their second year of life were found provided significant prediction of EL outcome at age four. Stepwise regression identified RL and presence of stereotypic and repetitive at the first visit as significantly associated with EL outcome. Implications of these findings for early identification and intervention are discussed.
Keywords: Autism; Autistic Disorder; Child, Preschool; Communication; Follow-Up Studies; Humans; Infant; Language; Language Disorders; Language Tests; Language Therapy; Observer Variation; Questionnaires; Severity of Illness Index; Toddlers; article; autism; dept.cmd; follow up; hospitalization; human; infant; interpersonal communication; language disability; language test; observer variation; preschool child; questionnaire; speech therapy

Production of syllable stress in speakers with autism spectrum disorders - Paul, Rhea; Bianchi, Nancy; Augustyn, Amy; Klin, Ami; Volkmar, Fred R. (Research in Autism Spectrum Disorders, 2008)
This paper reports a study of the ability to reproduce stress in a nonsense syllable imitation task by adolescent speakers with autism spectrum disorders (ASD), as compared to typically developing (TD) age-mates. Results are reported for both raters' judgments of the subjects' stress production, as well as acoustic measures of pitch range and duration during stressed and unstressed syllable production. Results reveal small but significant differences between speakers with ASD and typical speakers in both perceptual ratings of stress and instrumental measures of duration of syllables. The implications of these findings for understanding prosodic deficits in ASD are discussed. (C) 2007 Elsevier Ltd. All fights reserved.
Keywords: Autism; Prosody; Syllable stress; acoustics; adolescent; adult; article; autism; clinical article; controlled study; dept.cmd; feedback system; female; human; intelligence quotient; male; mental task; motor coordination; pitch; priority journal; school child; speech articulation; speech perception; task performance